Mitochondrial Targeting of Herbal Medicine in Chronic Kidney Disease - Li, Qing; Xing, Changying; Yuan, Yanggang (Frontiers in Pharmacology, 2021)
Chronic kidney disease (CKD) is a common progressive disease that is typically characterized by the permanent loss of nephrons and an eventual decline in glomerular filtration rate. CKD increases mortality and has a significant impact on the quality of life and the economy, which is becoming a major public health issue worldwide. Since current conventional-medicine treatment options for CKD are not satisfactory, many patients seek complementary and alternative medicine treatments including Traditional Chinese Medicine. Herbal medicine is often used to relieve symptoms of renal diseases in the clinic. The kidney is abundant in the number of mitochondria, which provide enough energy for renal function and metabolism. In recent years, a vital role for mitochondrial dysfunction has been suggested in CKD. Mitochondria have become a new target for the treatment of diseases. A growing number of studies have demonstrated herbal medicine could restore mitochondrial function and alleviate renal injury both in vivo and in vitro. In this review, we sum up the therapeutic effect of herbal medicine in CKD via targeting mitochondrial function. This implies future strategies in preventing CKD.